The Impact of Independent of Activity Daily Living among Stroke Patients on Caregivers Burden - Nikmatul Fadilah; Loetfia Dwi Rahariyani (Universitas Airlangga, 2019)
Introduction: Weakness among stroke patients causes obstacles when fulfilling their activities in daily living (ADL). This condition also has an impact on the caregivers who provide daily care at home. The purpose of this study was to analyze the effect of independent ADL among the stroke patients on caregiver burden.Methods: The study used an analytical design through a cross-sectional approach. The variables included independent ADL and caregiver burden. A sample of 120 caregivers was taken from 2 community health centers in Surabaya through simple random sampling. The instruments used were Zarit Burden's Interview Schedule and the Katz Index of Independent for ADL. Regression ordinal was used to analyze the influence of independent ADL among stroke patients on caregiver burden.Results: The results showed that the caregiver who take care of stroke patients with severe functional impairment will feel burdened 3 times more than no burden. Post-stroke care at home through a rehabilitation program plays an important role in improving the condition of patients and their families at home, especially the caregivers.Conclusion: Nurses in a community health center through the family health care pathway provide comprehensive bio-psycho-socio-spiritual care in the rehabilitation period as expected. They are expected to improve and maintain the fulfillment of human needs comprehensively for stroke patients and their caregivers, so the quality of life of stroke patients, caregivers and their families remains optimal.